A cost-benefit analysis of deforestation in the Brazilian Amazon - Lykke E. Andersen (Institute for Applied Economic Research (ipea), 2015)
This paper compares the Total Economic Value of standing Amazonian rain forest with the Net Present Value of alternative agricultural land uses. It is shown that, at the current level of deforestation, the potential benefits of deforestation are higher than the expected costs. As the level of deforestation increases, however, the global costs of deforestation will rise, and eventually pass the value of agricultural land. At that point, the international community will have to provide incentives to induce Brazil to preserve the remainder of its rain forest.
Keywords: 330